Business Analysis Of Home Industry Of Opak Crackers - Reflis Reflis; Eko Sumartono; Ellys Yuliarti; Ilham Abdul Rasid (Media Agribisnis, 2023)
Indonesia is an archipelagic country that has fertile soil and the soil is suitable for planting various kinds of food crops, one of which is cassava.Cassava (Manihot esculenta) has several advantages including being able to grow on dry and infertile land, relatively high disease resistance. Fresh cassava is an agricultural commodity with low economic value. In order to increase the economic value of cassava, an effort is needed to process cassava into processed products, namely opaque crackers. The purpose of this study is to determine income, the comparison between revenue and production costs is basedR/C ratio, a comparison between revenue and production costs based onB/C ratio on home industry Opaque crackers in Magelang Village. This research was conducted in Magelang Village, Kerkap District, North Bengkulu. This location was deliberately set with the consideration that Magelang Village is one of the opaque cracker producing centers. This study found that: 1). Total production sold by business actorshome industry opaque crackers in one production is 750 pieces with a selling price of Rp. 500 per chip, getting an average revenue in one production of Rp.375,000., with the average cost of producing one production of Rp. 130,159. So that you get income in one production of IDR 244,841. 2). Mark R/C system obtained is equal to 2.58 which means that according to the criteria of the R/C tester> 1, it can be concluded that the efforthome industry shrimp crisp Opaque in Magelang Village, Kerkap District, North Bengkulu Regency is profitable and feasible to cultivate. 3). MarkB/C ratio obtained by 1.58, whereB/C ratio in the business of making opaque crackers > 1, which is the interpretation that the efforthome industry Opak crackers in Magelang Village, Kerkap District, North Bengkulu Regency are financially feasible (earn profits) in running a business home industry opaque crackers.